2021
DOI: 10.1002/leg3.132
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of market participation and intensity of marketed surplus of smallholder chickpea producers in Este woreda

Abstract: In Ethiopia, chickpea is an important legume crop, particularly in Este district. It is a source of food and provides cash income for majority of smallholder farmers. To commercialize chickpea producers, selecting an appropriate market channel is important for participation. Hence, this study aimed to identifying factors affecting chickpea market participation and volume of marketed surplus of chickpea. Both primary and secondary sources of data were used. Moreover, both qualitative and quantitative data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
0
0
Order By: Relevance
“…When food price become high, some families may not have enough money to buy all the food they need but if the family have extra money that will be saved they may be afford more food. This is in line with the study of Worku et al ( 2021 ), lagged price of the agricultural product has a positive impact on household income.…”
Section: Resultssupporting
confidence: 92%
“…When food price become high, some families may not have enough money to buy all the food they need but if the family have extra money that will be saved they may be afford more food. This is in line with the study of Worku et al ( 2021 ), lagged price of the agricultural product has a positive impact on household income.…”
Section: Resultssupporting
confidence: 92%
“…These findings are in line with [17] who reported that aged farmers were less commercialized because they produce less due to labor requirements. However, the findings disagree with [18,19] who reported that older people are more enthusiastic and participate more on marketing as compared to young persons. Total land size owned by the smallholder farmers positively influenced common bean commercialization and was significant at 5% level of significance.…”
Section: Determinants Of Common Bean Commercializationcontrasting
confidence: 85%
“…Therefore, increased Niger seed production led to more Niger seed output commercialization. It aligns with Worku et al (2021), revealing that more producers entered the market as chickpea output rose. Hence, the amount of agricultural production was directly linked with the probability of agricultural output market participation.…”
Section: Determinants Of Niger Seed Commercializationsupporting
confidence: 57%
“…Agricultural extension services increased the skills and knowledge of farmers, assisting them in adopting modern technology and facilitating liquidity and input supply constraints (Lerman, 2004). Furthermore, it is supported by the findings of Worku et al (2021) that households with frequent contact with development agents were more likely to participate in the output market. In other words, the frequency of extension contact and agricultural commercialization had a direct relationship.…”
Section: Determinants Of Niger Seed Commercializationmentioning
confidence: 83%